Integrative couple therapy in action: A practical guide for handling common relationship problems and crises: by Arthur Nielsen, New York, Routledge, 2022, 284 pp., $159.98 (hardcover); $34.60 (paperback); $31.78 (ebook), ISBN: 9781032272160 (hbk); ISBN: 9781032272177 (pbk); ISBN: 978100329184 (ebk) - Nielsen, Arthur (Psychoanalysis: Self & Context)
"Integrative Couple Therapy in Action: A Practical Guide for Handling Common Relationship Problems and Crises" by Arthur Nielsen is a comprehensive book that offers an integrative approach to couple therapy. The author draws from various perspectives, including systemic, psychodynamic, and behavioral approaches, to provide practical skills for handling conflict and self-exploration experiences. The book addresses common relationship problems such as sex, money, children, work, and time pressures, as well as more severe issues like extramarital affairs, divorce, and stepfamilies. Nielsen emphasizes the importance of domain-specific knowledge and detailed study of specific relationship problems in achieving successful therapeutic outcomes.